A Response to Armstrong and Read, Poirine and Bertram - Jerome L. McElroy (Island Studies Journal, 2014)
This is a brief response to Armstrong and Read, Poirine, and Bertram, synthesizing their welcome thoughtful remarks in response to my paper, and briefly outlining the way forward that research in this area of island studies could take.